2000
DOI: 10.1016/s0735-1097(99)00648-8
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and long-term outcome of intracoronary stent implantation for true bifurcation lesions

Abstract: Stenting of bifurcation lesions can be achieved with a high success rate. However, stenting of both branches offers no advantage over stenting one branch and performing balloon angioplasty of the other branch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
145
1
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(162 citation statements)
references
References 31 publications
8
145
1
8
Order By: Relevance
“…Coronary bifurcation lesions account for up to 15%-20% of all current percutaneous revascularizations, and represent challenging subsets, with lower rates of angiographic and procedural success [14][15][16]. Given the relative frequency and the overall complexity of coronary bifurcation lesions, many works have addressed this topic, focusing mainly on stenting techniques, and BMS vs. DES use [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary bifurcation lesions account for up to 15%-20% of all current percutaneous revascularizations, and represent challenging subsets, with lower rates of angiographic and procedural success [14][15][16]. Given the relative frequency and the overall complexity of coronary bifurcation lesions, many works have addressed this topic, focusing mainly on stenting techniques, and BMS vs. DES use [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…30-day outcomes did not show significant differences in MACE rates, with 1.0% in the ≤45 years group and 2.1% in the >45 years group (p=0.439), with death in 0.5% and 1.2% (p=0.388). At long-term follow-up (24.4± 15.1 months), younger patients showed similar rates of MACE, (12.8% vs. 16.6%, p=0.161), myocardial infarction (3.1% vs. 3.7%, p=0.633), target lesion revascularization (11.3% vs. 12.5%, p =0.627), or stent International Journal of Cardiology xxx (2012) xxx-xxx ☆ All authors take responsibility for all aspects of the reliability and freedom from bias of the data presented and their discussed interpretation. ⁎ Corresponding author at: Cardiology, University of Modena and Reggio Emilia, Via del Pozzo 71, 41124 Modena, Italy.…”
mentioning
confidence: 85%
“…Furthermore, patients with long sidebranch lesions were systematically excluded from the randomized trials [4]. Registries, though available in greater numbers [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], are of variable quality and use different lesion classification systems, quantitative coronary angiography (QCA) measurements performed in unclear technical conditions, with identical technical strategies bearing different names or different techniques grouped under a single name. Other than the comparison between stent deployment in one versus two branches, a meta-analysis of these various reports has proven quite impossible.…”
Section: Introductionmentioning
confidence: 99%
“…2 -4 Specifically, the use of bare metal stents (BMSs) for both branches has not improved the results compared with 1-stent plus the kissing balloon technique. 5,6 Recently, several randomized and controlled trials have demonstrated great advantages of drug-eluting stents (DESs) in significantly reducing restenosis and recurrence of symptoms, and improving clinical outcomes after percutaneous coronary intervention (PCI). 7,8 Little is known about the comparative effects of 1-DES plus the kissing balloon technique with the 2-DES for bifurcation angioplasty in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%